Exploring volatility transmission in Capesize freight contracts: Insights from energy and commodity markets - Jackson Jinhong Mi; Shek Ahmed; Yanhui Chen (PLoS ONE, 2025)
Analyzing the interactions between spot and time charter freight is crucial for the maritime industry. While numerous studies have explored the relationship between average freight indices and spillover effects, a gap remains in understanding the deeper connections between inter-regional shipping routes and chartering contracts. This research investigates the role of Capesize freight dynamics in shaping the regional dry bulk freight market, with a focus on the influence of energy and commodity price fluctuations. Utilizing the TVP-VAR model, we identify distinct trends across various investment horizons. The analysis reveals that short-term spillovers dominate the system, with crude oil serving as a consistent shock transmitter within the time charter network. The China-Brazil route drives spillovers across all periods, while the Australia-China route transitions from absorbing short-term volatility to transmitting long-term shocks. Similarly, the Tubarão-Rotterdam and Bolivar-Rotterdam routes display comparable shifts, transmitting short-term spillovers but absorbing long-term volatility. These findings offer valuable insights for stakeholders seeking to manage risks amidst economic and geopolitical uncertainties.